Domestic violence and suicide in India. (May 2022) - Garcia, Eveline Cruz; Vieira, Pedro Suyã Costa; de Andrade Viana, Raízza Caroline; Mariano, Felipe Cardoso; de Brito, Mara Iany Braga; de Araújo Feitosa Neto, Jose; Lima, Nadia Nara Rolim; Neto, Modesto Leite Rolim
Abstract: India has the highest number of suicides in the world. Indian men account for a quarter of global suicides, while Indian women account for 36% of all global suicides in the 15–39 age group. One suicide every 25 min. These are not isolated incidents. Mental health experts say that one of the main reasons for this situation is rampant domestic violence. India's official data are hugely underestimated and do not convey the true scale of the problem. Women from this country are responsible for 36% of global female suicide deaths. In a country like India, with its wide sociocultural variations, there can be multiple risk factors: hanging, pesticide consumption, drug overdose, and self-immolation. Access to these "lethal" resources is an important factor. Highlights: Children make up more than half (57%) of the population in need of emergency humanitarian assistance in Afghanistan. Afghan children grow up with the constant threat of violence and face numerous other rights violations. As many as 3.5 million children inside Afghanistan are currently out of school. Than a third of children have been exposed to psychological distress